Politico-ideological violence: zooming in on grievances - Ajil, Ahmed (European journal of criminology, 2022)
Most studies on politico-ideological violence (PIV) recognize the importance of socio-political and economic grievances, but they rarely analyse them in depth. I argue that this is symptomatic of a tendency of depoliticization in radicalization research in the post 9/11 context and suggest that the study of PIV may benefit from putting greater emphasis on the element of grievance. A grievance-based analysis allows for critical and reflexive consideration of structural and systemic factors pertinent for engagement in PIV and may thereby contribute to demystifying and re-politicizing the current debate on PIV. I propose three ‘ideal types’ of grievances (racial, ethnic and religious; socio-economic; political), which may be locally or globally oriented or inspired, and suggest that a combination of those is likely to be present in most forms of PIV. I conclude with a few methodological reflections and potential implications for policymaking.